Aerosol climate change effects on land ecosystem services. (2nd June 2017) - Unger, N.; Yue, X.; Harper, K. L.
Abstract : A coupled global aerosol–carbon–climate model is applied to assess the impacts of aerosol physical climate change on the land ecosystem services gross primary productivity (GPP) and net primary productivity (NPP) in the 1996–2005 period. Aerosol impacts are quantified on an annual mean basis relative to the hypothetical aerosol-free world in 1996–2005, the global climate state in the absence of the historical rise in aerosol pollution. We examine the separate and combined roles of fast feedbacks associated with the land and slow feedbacks associated with the ocean. We consider all fossil fuel, biofuel and biomass burning aerosol emission sources as anthropogenic. The effective radiative forcing for aerosol–radiation interactions is −0.44 W m −2 and aerosol–cloud interactions is −1.64 W m −2 . Aerosols cool and dry the global climate system by −0.8 °C and −0.08 mm per day relative to the aerosol-free world. Without aerosol pollution, human-induced global warming since the preindustrial would have already exceeded the 1.5 °C aspirational limit set in the Paris Agreement by the 1996–2005 decade. Aerosol climate impacts on the global average land ecosystem services are small due to large opposite sign effects in the tropical and boreal biomes. Aerosol slow feedbacks associated with the ocean strongly dominate impacts in the Amazon and North American Boreal. Aerosol cooling of the Amazon by −1.2 °C drives NPP increases of 8% or +0.76 ± 0.61 PgC per year, a 5–10 times larger impact than estimates of diffuse radiation fertilization by biomass burning aerosol in this region. The North American Boreal suffers GPP and NPP decreases of 35% due to aerosol-induced cooling and drying (−1.6 °C, −0.14 mm per day). Aerosol–land feedbacks play a larger role in the eastern US and Central Africa. Our study identifies an eco-climate teleconnection in the polluted earth system: the rise of the northern hemisphere mid-latitude reflective aerosol pollution layer causes long range cooling that protects Amazon NPP by 8% and suppresses boreal NPP by 35%.